Relevansi Pendidikan Islam - Dewi, Azzahra Kusuma; Sultani, Dalmi Iskandar (Jurnal Penelitian Multidisiplin Ilmu, 2025)
The research aims to determine the relevance of Islamic education in implementing Islamic values ??in the educational environment and modern life, especially in spiritual, moral and social aspects. Using library methods, and data collection using content analysis. The results of the study indicate that the values ??of character education in Islam, namely honesty, trustworthiness, tolerance, and responsibility, provide real contributions in creating a generation that is knowledgeable, moral, and responsible in living life as social beings. So that Islamic education remains relevant to be applied as a foundation for humans in building a civilization that is balanced between material progress and spiritual maturity.